Relationship between Age and Sex with Histopathological Differentiation of Colorectal Adenocarcinoma - Sugiarto, Sugiarto; Nurfitriana, Alifia; Marindawati, Mieke (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2022)
Background: Colorectal cancer is one of the most common cancers causing morbidity in both women and men. There is a tendency for women over 65 to show higher mortality and lower 5-year survival rate from colorectal cancer than their male counterparts of the same age. Purposes: To find out the relationship between age and sex with the degree of differentiation of colorectal adenocarcinoma in the Anatomical Pathology Laboratory of General Hospital of Cengkareng in 2015 – 2019. Methods: This study used a analytic study with a retrospective approach, with secondary data from the medical records of anatomic pathology examination results in colorectal adenocarcinoma patients in General Hospital of Cengkareng in 2019. Result: Based on the result of the chi-square statistical test, the relationship between age and the degree of differentiation of colorectal adenocarcinomas was found to be p-value 0.476 (a0.05). Whereas the relationship between sex with the degree of colorectal adenocarcinoma was found to be p-value 0.049 (a0.05). Conclusion: There is no relationship between age and the degree of differentiation of colorectal adenocarcinomas, but gender have correlation.